Polyurethane nanocomposites with click-coupled nanodiamonds exhibiting enhanced mechanical and shape memory effects - Yoo, Hye Jin; Lee, Byung Hak; Mahapatra, Sibdas Singha; Yang, Cheol-Min; Cho, Jae Whan (WILEY, 2017)
Poly(-caprolactone)diol (PCL)-functionalized nanodiamonds (f-NDs) were synthesized using a click chemistry reaction between the azide-moiety PCL and alkyne-moiety NDs and were incorporated into shape memory polyurethane (PU) at f-ND concentrations of 0, 0.5, 1, and 2 wt % to produce high-performance shape memory nanocomposites. The PU/f-ND nanocomposites exhibited better shape recovery, shape recovery stress, and breaking stresses than pure PU. Shape recovery of greater than 95% was demonstrated for all the nanocomposites in the third cycle, and the shape recovery stresses increased significantly with the f-ND content. These enhanced mechanical and shape recovery properties are ascribed to increased interactions between the f-NDs and PU matrix due to incorporation of click-coupled f-NDs. The click-coupled NDs can be used as nanofillers to enhance the mechanical and shape memory properties of polymers. (c) 2017 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2017, 134, 45465.
Keywords: WALLED CARBON NANOTUBES; POLYMER NANOCOMPOSITES; YOUNGS MODULUS; CHEMISTRY; GRAPHENE; COMPOSITES; PERFORMANCE; NANOFIBERS; HYDROGELS; DELIVERY